Digital radio, a learning dynamic for social communicators at the University of Guayaquil - Alarcón Quiñónez, Antonia Lorena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Digital platforms have become a priority in the development of communication, being vital for traditional media to offer a service that allows access to their content at any time, day or place, even allowing them to create a close connection with the public. Radio "La U Online" is a format that appears as the vanguard of digital communication at the University of Guayaquil, based on the academic project of the faculty of social communication. The intention of the communication career is to create this resource for practices pre-professional training of students, interacting with all the academic units of the university.